Clinical spectrum of acute kidney injury among hospitalized patients in coastal districts of Andhra Pradesh - Vaddadi Suresh; NSRC Gupta; E Usha Bhargavi (International Journal of Medical Research and Review, 2016)
Introduction: Acute kidney injury (AKI) is one of the important overall causes of mortality in hospitalized patients. Variability in definitions of AKI has led to gross variations in the incidence across the world. Multiple metabolic derangements in these patients can increase the mortality and morbidity. Our study aims at studying the incidence, clinical, biochemical, hematological and sonographic abnormalities seen in hospitalized patients with AKI.Acute Kidney InjuryMethods and Material: Case records of 237 patients admitted in various departments of a tertiary care center over a three year period from 2010 to 2013, who developed AKI were included in the study. The etiologies, various hematological and biochemical test reports, ultrasonography of abdomen and treatment given was noted. Statistical analysis was done to find the pattern of AKI and the prevalence of various biochemical and metabolic abnormalities.Results: The incidence of AKI among hospitalized patients was 1.9%. Out of 237 patients with AKI, 62% were males. 70% belonged to medical and allied specialties. The most common cause of AKI was infection related. Fever was the most common symptom (48%) and common laboratory abnormalities included anemia (70%), hyperkalemia (36%) and proteinuria (29%). Mortality in this study was 21 (9%), 73% received conservative therapy while 27% had undergone hemodialysis.Conclusions: AKI is highly prevalent among hospitalized patients admitted in medical and allied departments. Infections top the list among the causes of AKI. Various metabolic and biochemical abnormalities are seen, most of them can be managed conservatively and up to one third may require hemodialysis.